Scalable generation of large-scale unstructured meshes by a novel domain decomposition approach. (July 2018) - Chen, Jianjun; Xiao, Zhoufang; Zheng, Yao; Zou, Jianfeng; Zhao, Dawei; Yao, Yufeng
Highlights: Inputting a CAD model, the proposed approach executes the subsequent meshing steps in a fully parallel and automatic manner. The most time-consuming steps of domain decomposition have been parallelized. The finally generated surface mesh is defined on the input CAD model. The shape quality of inter-domain interfaces is reasonable; thus, the parallel mesh improvement algorithm can fix them without compromising mesh quality. A more scalable parallel performance is observed by detailed comparisons with state-of-the-arts approaches. Abstract: A parallel algorithm is proposed for scalable generation of large-scale tetrahedral meshes. The key innovation is the use of a mesh-simplification based domain decomposition approach. This approach works on a background mesh with both its surface and its interior elements much larger than the final elements desired, and decomposes the domain into subdomains containing no undesirable geometric features in the inter-domain interfaces. In this way, the most time-consuming part of domain decomposition can be efficiently parallelized, and other sequential parts consume reasonably limited computing time since they treat a very coarse background mesh. Meanwhile, the subsequent parallel procedures of mesh generation and improvement are most efficient because they can treat individual subdomains without compromising element quality. Compared with published state-of-the-art parallel algorithms, the developed parallel algorithm can reduce the clock time required by the creation of one billion elements on 512 computer cores from roughly half an hour to less than 4 minutes.